Implementasi Constrained Application Protocol (CoAP) pada Sistem Pengamatan Kelembaban Tanah - Yosef Febri Wiryawan; Dany Primanita Kartikasari; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Recently, technology has been developed to facilitate human life in every aspects including agriculture. Implementation of technology in agriculture is still left behind for example in terms of observation soil moisture. Based on concept of Wireless Sensor Network (WSN) we can make a suitable network architecture to solve the problem. Wireless Sensor Network (WSN) is one of the emerging technologies which combine sensors and tiny embedded devices over a wireless communication medium. The aim of this study is how to make a reliable communication for the system. To accomplish our objectives, we implemented a lighweight protocol as a web transfer protocol named Constrained Application Protocol (CoAP) for the system. To collect the soil moisture data we integrated Microcontroller Wemos D1 and sensor YL-69 to perform as a sensor node, it sends sensing data to the server with bluetooth module HC-05. Then servers and clients will exchange data wirelessly using the CoAP protocol. To see the performance of the CoAP protocol, we tested the data exchanging that occurs between server and client in several scenarios. The test result revealed there is a significant increase of delay in payload size more than 64 bytes because of process blockwise mechanism in CoAP protocol. In addition, distance can also increase the delay in data transmission process.